A dual approach to compatibilize PLA/ABS immiscible blends with epoxidized cardanol derivatives. (May 2019) - Rigoussen, Alan; Raquez, Jean-Marie; Dubois, Philippe; Verge, Pierre
Graphical abstract: Highlights: PLA and ABS were mixed by reactive extrusion with epoxidized cardanol compounds. Epoxidized cardanol and its mixture with raw cardanol were tested. Both approach led a substantial increase of the compatibility of PLA and ABS. The mixture led a synergistic effect on the mechanical properties. Impact strength increased of 172% and strain at break more than 1000% vs PLA. Abstract: With the aim to reinforce polylactide (PLA) mechanical properties, poly(acrylonitrile-butadienestyrene) (ABS) is considered as a polymer of choice. However, PLA and ABS are immiscible, leading to blends with weak properties. Cardanol is a lipid phenolic known to compatibilize these two polymers thanks to its reaction with ABS, but does not react with PLA and restricts its use to the modification of ABS. In this work, we investigated the effect of cardanol-based compatibilizers able to react by reactive extrusion with both PLA and ABS. In a first approach, cardanol unsaturations were epoxidized (CardE), hoping to react with PLA, while cardanol phenolic group would react with ABS. This compatibilizer was efficient as attested by ABS nodules size reduction and dispersion within PLA, in addition to the merging of the relaxation temperatures of both polymers at 69.5 °C when 5 wt% CardE was used. In addition, it led to a substantial improvement of PLA/ABS impact strength and elongation at break. In a second approach, we used of a mixture of compatibilizers, containing raw and epoxidized cardanol, both of them reacting either with PLA or with ABS. Here, a clear synergistic effect was observed, as attested by the exceptional increases of both impact strength (+172% compared to neat PLA) and elongation at break (+1000% compared to neat PLA). We assumed modified chains of both PLA and ABS with cardanol derivatives during reactive extrusion would intersperse between PLA and ABS, reducing the interfacial tension and improving the interfacial adhesion, leading to the outstanding compatibilization of the blend.